2023
DOI: 10.1175/jcli-d-22-0704.1
|View full text |Cite
|
Sign up to set email alerts
|

Interdecadal Change of Tropical Cyclone Translation Speed during Peak Season in South China Sea: Observed Evidence, Model Results, and Possible Mechanism

Abstract: Long-term variations in the translation speed of tropical cyclones (TCs) in the South China Sea (SCS) are examined based on five TC datasets from different institutions. TC translation speed during the TC peak season in the SCS shows an evident rhythm of interdecadal change throughout 1977–2020. This interdecadal change in TC translation speed in the SCS can be well reproduced by a newly developed trajectory model. The model results indicate that the interdecadal change in TC translation speed is primarily due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…When the PDO is in the warm phase, the east Pacific SST is warm and the west Pacific SST is cold; the probability of the tropical cyclone genesis regions being controlled by the subtropical high and its downdrafts is high, and thus, not conducive to the development of typhoons. The above further verifies the more recent finding by Shan et al that interdecadal variation in the movement speed of typhoons in the South China Sea is related to variations in the steering airflow driven by the east-west SST gradient [51]. The abnormal mode of the Pacific SST is closely related to the cross-equatorial airflow.…”
Section: Sst and Subtropical Highsupporting
confidence: 88%
“…When the PDO is in the warm phase, the east Pacific SST is warm and the west Pacific SST is cold; the probability of the tropical cyclone genesis regions being controlled by the subtropical high and its downdrafts is high, and thus, not conducive to the development of typhoons. The above further verifies the more recent finding by Shan et al that interdecadal variation in the movement speed of typhoons in the South China Sea is related to variations in the steering airflow driven by the east-west SST gradient [51]. The abnormal mode of the Pacific SST is closely related to the cross-equatorial airflow.…”
Section: Sst and Subtropical Highsupporting
confidence: 88%
“…Previous studies have investigated the long-term changes in the intensity and PDI of TCs that have made landfall in southern China. Some studies have found no significant trends in the intensity or PDI [19,70], while Liu and Chan [8,18] studied the destructive power of TCs when they made landfall in southern China and found that the destructive power during landfall was lower than at other times during the period from 1997 to 2011. The factors that regulate the interdecadal changes in the destructive power of TCs when they make landfall are changes in vertical wind shear and ocean thermal potential [8,18,71].…”
Section: Significance and Innovation Of This Studymentioning
confidence: 99%
“…This decrease in intensity has been attributed to the vertical moisture transport. Recent research has also focused on the movement speed of TCs in the SCS and has found that the movement speed was lower during the period from the early 1990s to the early 2000s compared to other periods [18].…”
Section: Introductionmentioning
confidence: 99%
“…The MT migrates northward during summer and displaces southward during fall (Chen et al, 2017). TC activity is normally investigated for its salient feature in the peak JAS season (Lai et al, 2022(Lai et al, , 2023Shan & Yu, 2023) or its gross feature in the broader JJASO period (Chu et al, 2010;Tu et al, 2009). In the former approach, variability features of TC activity may be further compared between the peak JAS and post-peak October-December (OND) seasons (Feng et al, 2021;Shan & Yu, 2021).…”
Section: Interdecadal Variability Of Meridional Tc Genesis In the Wnpmentioning
confidence: 99%